Artificial Intelligence with Mirror Exchange for Libraries - Bustomi, Rizki (Abdi Masyarakat, 2024)
Advances in information technology must be balanced with the progress of the times. The development of information technology is currently very rapid, the various sources of information currently circulating are not necessarily accurate in their information content. Currently, there are various innovations and creativity in information technology that bring benefits to humanity in general, whether felt directly or indirectly, the world of information today seems to be inseparable from technology. The use of technology by society makes the world of technology increasingly sophisticated. One of them is in the field of communication technology, such as smartphones and the internet, making people increasingly improve their way of communicating. Various kinds of media for communication also exist to make it easier for humans to interact. As time goes by, internet technology has become a necessity for society, one of which is smartphones, all of which are based on Android. Libraries are a source of accurate and reliable information that the public can use directly to make the nation and state smarter. Various kinds of innovations have been created in this world to make everyday life easier. Libraries exist as sources of information whose accuracy is guaranteed and reliable. responsible for collections both printed and recorded, the current trend of libraries when viewed from the collection format has undergone a significant change, namely from conventional libraries to Hydrid, Digital and Bookless libraries, Hydrid Libraries have printed and recorded as well as online collections, while digital libraries provide access to users. remote and easily accessible, bookless libraries are more about providing facilities such as laptops, desktops with applications and providing e-readers to users. In this modern era, innovation and creativity are needed to provide solutions to every existing problem and become a breakthrough in accelerating the implementation of activities in every library management throughout the world. One of the innovations carried out is by using a smartphone or what we usually know as a smartphone, where the smartphone functions as a reader of all kinds of objects written on paper or other media, by mirroring/pasting the smartphone monitor screen onto books and so on. . and then went on about all sorts of things. The information that has been read will be transferred via a special system application that is connected to the smartphone screen. The working principle is like a lens on a camera, namely by strengthening autofocus on every written object that is reflected on the smart screen. tphone, so that all existing information will be transferred in full to the application that has been prepared. The implementation of this innovation needs to be supported by a special application that is capable of receiving input, processing and output from the smartphone monitor screen to a MARC-based information data processing application so that all kinds of metadata in every information exchange remains intact. exchange of information, the use of artificial intelligence with this exchange mirror will be useful in carrying out library management, starting from recording, processing library materials, storing library materials, servicing library materials, preserving library materials and retrieving library material information in addition to library management. This innovation can also be used in carrying out all kinds of archiving of every important document. and others. This innovation is expected to create new methods in library management in every line of existing activities, apart from being an effective and efficient step in accelerating library management, it also saves costs and library personnel.